Perancangan Interior Area Bermain Untuk Anak Pra Sekolah di Surabaya - Angelie Nathalia; Stephanus Pantja Honggowidjaja; Mohammad Taufan Rizqy (Intra, 2019)
Playground is a useful place for children to explore, play and spend time with their friends. Every playground has a character and purpose, which causes every playgrounds have different sensations. Therefore, the design of the playground itself must have an exciting and educational activity, especially for early childhood. The role of a game is very important for children's intelligence from motoric, cognitive, and affective aspects. At early age the physical growth and development of the child's brain is very rapid. So playing and learning is an activity that deserves to be created into an area or building.